Institutional evaluation: politicies of evaluation of distance learning in Brazil (Research, Society and Development, 2016)
This paper aims to analyze the public politicies of Teachers' Education through Distance Learning, focusing on the external evaluation of Distance Learning Formation of teachers of Visual Arts. This reflection intends to understand the relation between the results of external evaluation and the major objective of public politicies, which is the quality improvement of that formation. The study was based on legal documents and on the regulation determined by the National Institute of Studies and Research – Ministry of Education and Culture - MEC, Benchmarks of Quality for Distance Learning, National Curricular Guidelines of Arts, National Evaluation System of Higher Education, National Commission for the Evaluation of Higher Education and on authors like Azevedo; Sathler (2004), Assis and Amaral (2004), Dias Sobrinho (2002), Cervi e Torres (2009), Lopes (2004), Maia and Mattar (2007) among others. Through the development of the present study, it was possible to observe that, even though evaluation takes place through different modalities, the result of evaluations of Distance Learning Courses are not disclosed separately from the Classroom-based modality.